Adversity intelligence, family support, and quarter life crisis in individuals who married at a young age - Rokhmatun, Amanda; Salsabila, Mustamira Sofa; Yulianti, Iin (Universitas Sarjanawiyata Tamansiswa, 2024)
The phenomenon of early marriage is characterized by various challenges caused by various factors, one of which is psychological unpreparedness. Getting married at a young age is closely related to the problem of quarter life crisis (QLC). QLC is an emotional crisis that occurs at the age of 18-29 years who experience unstable conditions such as indecisiveness, a variety of choices, and even feelings of giving up easily. QLC is influenced by internal and external factors, in this research it focuses on adversity intelligence (internal) and family support (external). This study aims to analyze the relationship between adversity intelligence and family support with QLC in individuals who marry at a young age. This research uses quantitative methods with a sampling technique, namely purposive sampling. The subjects of this research were 50 individuals who married at an early age. Data were collected using the quarter life crisis scale, adversity intelligence scale and family support scale which were analyzed using multiple regression analysis with the help of JASP 16.2 for Windows software. The research results show a value of r = 0.762 with p < 0.001, meaning that there is a significant relationship between the variables of adversity intelligence and family support and the quarter life crisis in individuals who marry at a young age with an effective contribution of 58%. Based on the results of this research, suggestions for further research are expected to control personality traits in reviewing the QLC that occurs in individuals who marry at a young age.